2017
DOI: 10.1016/j.ocecoaman.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The joint effect of tidal barrier construction and freshwater releases on the macrobenthos community in the northern Yellow River Delta (China)

Abstract: a b s t r a c tTidal barriers isolate intertidal areas from tides, creating distinct conditions on either side of the barrier, and freshwater releases change the receiving area's hydrology and salinity. However, the combined effect of these human actions is unknown. Using the macrobenthos community as a bioindicator, we sampled part of the northern Yellow River Delta that has been managed using tidal barriers and freshwater releases, in the spring and autumn of 2014, before and after the summer freshwater rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Our latest research also found that decreased sediment salinity made it possible for many oligohaline species, such as Chironomus sp. and Cladotanytarsus mancus, to live in the areas with lower salinity inside the tidal barriers (Yang et al, 2016). Our results indicate that seashore reclamation and other human impacts have had a negative influence on the number of species, biomass, and abundance of the macrobenthos.…”
Section: Relationships Between Reclamation Intensity and The Macrobenmentioning
confidence: 71%
“…Our latest research also found that decreased sediment salinity made it possible for many oligohaline species, such as Chironomus sp. and Cladotanytarsus mancus, to live in the areas with lower salinity inside the tidal barriers (Yang et al, 2016). Our results indicate that seashore reclamation and other human impacts have had a negative influence on the number of species, biomass, and abundance of the macrobenthos.…”
Section: Relationships Between Reclamation Intensity and The Macrobenmentioning
confidence: 71%